Impact of remote telemedical management on mortality and hospitalizations in ambulatory patients with chronic heart failure: the telemedical interventional monitoring in heart failure study - Koehler, Friedrich; Winkler, Sebastian; Schieber, Michael; Sechtem, Udo; Stangl, Karl; Böhm, Michael; Boll, Herbert; Baumann, Gert; Honold, Marcus; Koehler, Kerstin; Gelbrich, Goetz; Kirwan, Bridget-Anne; et al. (Circulation (New York, N.Y.), 2011)
This study was designed to determine whether physician-led remote telemedical management (RTM) compared with usual care would result in reduced mortality in ambulatory patients with chronic heart failure (HF). We enrolled 710 stable chronic HF patients in New York Heart Association functional class II or III with a left ventricular ejection fraction ≤35% and a history of HF decompensation within the previous 2 years or with a left ventricular ejection fraction ≤25%. Patients were randomly assigned (1:1) to RTM or usual care. Remote telemedical management used portable devices for ECG, blood pressure, and body weight measurements connected to a personal digital assistant that sent automated encrypted transmission via cell phones to the telemedical centers. The primary end point was death from any cause. The first secondary end point was a composite of cardiovascular death and hospitalization for HF. Baseline characteristics were similar between the RTM (n=354) and control (n=356) groups. Of the patients assigned to RTM, 287 (81%) were at least 70% compliant with daily data transfers and no break for >30 days (except during hospitalizations). The median follow-up was 26 months (minimum 12), and was 99.9% complete. Compared with usual care, RTM had no significant effect on all-cause mortality (hazard ratio, 0.97; 95% confidence interval, 0.67 to 1.41; P=0.87) or on cardiovascular death or HF hospitalization (hazard ratio, 0.89; 95% confidence interval, 0.67 to 1.19; P=0.44). In ambulatory patients with chronic HF, RTM compared with usual care was not associated with a reduction in all-cause mortality. URL: http://www.ClinicalTrials.gov. Unique identifier: NCT00543881.